Determination of Dynamics of Plant Plasma Membrane Proteins with Fluorescence Recovery and Raster Image Correlation Spectroscopy - Laňková, Martina; Humpolíčková, Jana; Vosolsobě, Stanislav; Cit, Zdeněk; Lacek, Jozef; Čovan, Martin; Čovanová, Milada; Hof, Martin; Petrášek, Jan (Microscopy and microanalysis, 2016)
A number of fluorescence microscopy techniques are described to study dynamics of fluorescently labeled proteins, lipids, nucleic acids, and whole organelles. However, for studies of plant plasma membrane (PM) proteins, the number of these techniques is still limited because of the high complexity of processes that determine the dynamics of PM proteins and the existence of cell wall. Here, we report on the usage of raster image correlation spectroscopy (RICS) for studies of integral PM proteins in suspension-cultured tobacco cells and show its potential in comparison with the more widely used fluorescence recovery after photobleaching method. For RICS, a set of microscopy images is obtained by single-photon confocal laser scanning microscopy (CLSM). Fluorescence fluctuations are subsequently correlated between individual pixels and the information on protein mobility are extracted using a model that considers processes generating the fluctuations such as diffusion and chemical binding reactions. As we show here using an example of two integral PM transporters of the plant hormone auxin, RICS uncovered their distinct short-distance lateral mobility within the PM that is dependent on cytoskeleton and sterol composition of the PM. RICS, which is routinely accessible on modern CLSM instruments, thus represents a valuable approach for studies of dynamics of PM proteins in plants.
Keywords: buněčná membrána; Nicotiana; Membrane Proteins; Microscopy, Confocal; auxin efflux; konfokální mikroskopie; auxin influx; plasma membrane; počítačové zpracování obrazu; Image Processing, Computer-Assisted; spektrální analýza; raster image correlation spectroscopy; tabák; Plant Cells; membránové proteiny; Spectrum Analysis; fluorescence recovery after photobleaching; Cell Membrane; rostlinné buňky